Embedded Interaction: The Accomplishment of Actions in Everyday and Video-Mediated Environments - Luff, P; Jirotka, M; Yamashita, N; Kuzuoka, H; Heath, C; Eden, G (2013)
A concern with "embodied action" has informed both the analysis of everyday action through technologies and also suggested ways of designing innovative systems. In this article, we consider how these two programs, the analysis of everyday embodied interaction on the one hand, and the analysis of technically-mediated embodied interaction on the other, are interlinked. We draw on studies of everyday interaction to reveal how embodied conduct is embedded in the environment. We then consider a collaborative technology that attempts to provide a coherent way of presenting life-sized embodiments of participants alongside particular features of the environment. These analyses suggest that conceptions of embodied action should take account of the interactional accomplishment of activities and how these are embedded in the material environment. © 2013 ACM.